2018
DOI: 10.1093/nar/gky496
|View full text |Cite|
|
Sign up to set email alerts
|

Argonaute-based programmable RNase as a tool for cleavage of highly-structured RNA

Abstract: The recent identification and development of RNA-guided enzymes for programmable cleavage of target nucleic acids offers exciting possibilities for both therapeutic and biotechnological applications. However, critical challenges such as expensive guide RNAs and inability to predict the efficiency of target recognition, especially for highly-structured RNAs, remain to be addressed. Here, we introduce a programmable RNA restriction enzyme, based on a budding yeast Argonaute (AGO), programmed with cost-effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
(55 reference statements)
0
30
0
Order By: Relevance
“…Previous studies of eAgos and several mesophilic pAgos showed that mismatches between the guide and target strands may have large effects on the cleavage efficiency and precision ( 25 , 32 ). To study the effect of mismatches on target cleavage, we designed a set of DNA and RNA guides, each containing a single mismatched nucleotide at a certain position ( Supplementary Table S1 ), and tested them in the cleavage reaction with KmAgo (Figure 5 and Supplementary Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of eAgos and several mesophilic pAgos showed that mismatches between the guide and target strands may have large effects on the cleavage efficiency and precision ( 25 , 32 ). To study the effect of mismatches on target cleavage, we designed a set of DNA and RNA guides, each containing a single mismatched nucleotide at a certain position ( Supplementary Table S1 ), and tested them in the cleavage reaction with KmAgo (Figure 5 and Supplementary Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dayeh et al. reported that HIV-1 ΔDIS 5′UTR is a highly structured RNA (see Supplementary Table S2 ) ( 32 ). The HIV-1 ΔDIS 5′UTR was in vitro transcribed using T7 RNA polymerase and synthetic DNA templates carrying a T7 promoter sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work should motivate studies to test other G analogues (especially non‐azide/alkyne initiators such as 5′‐hydrazinyl‐5′‐deoxyguanosine), and determine whether a common 10‐nt leader/initiating sequence rich in A, C, or U would afford high yields of RNAs initiated with different G analogues. The use of programmable RNases (e.g., Argonautes loaded with defined DNA guides) for site‐specific cleavage of large RNAs and the generation of smaller cleavage products bearing the 5′‐G analogue initiator also merits consideration.…”
Section: Figurementioning
confidence: 99%
“…Some truncated versions of approximately half the size (short Agos) exist in nature22 . We speculate that it will be possible to truncate them further as Ago-PAINT only relies on the property of pre-forming the helix structure of the imager strand and a variant from Kluyveromyces polysporus that contains only the C-lobe was reported to retain almost all the binding properties of the untruncated version 35.…”
mentioning
confidence: 99%